AKAR KRISIS LINGKUNGAN HIDUP - Yohanes I Wayan Marianta (Studia Philosophica et Theologica, 2011)
In this article, the author discusses environmental crisis, an unintended consequence of modern civilization, in terms of risk. The root causes of the crisis, namely domination of nature, population explosion, and growth-manic capitalist system, need to be properly addressed to avoid societal collapse. Environmental crisis threatens the sustainability of human civilization. Current environmental degradation, thus, must be regarded as a wake-up call for human societies to move toward ecological civilization